CIVIL LAW AND NEW REALITIES: DIGITIZATION AND ARTIFICIAL INTELLIGENCE - Pohrebniak, Mariia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to conduct a comprehensive analysis of the transformations in civil law under the influence of digitalization, the development of artificial intelligence, and emerging digital technologies. Methods: systemic-structural, comparative legal, analytical methods, as well as methods of legal modeling, generalization, and interpretation. Results: the main directions of civil law transformation in the context of the digital economy have been identified. The study outlines the need to reconsider legal subjectivity, the legal status of artificial intelligence, the adaptation of contract and tort law, and the regulatory framework for digital assets and personal data protection. Discussion: the necessity of updating Ukraine’s civil legislation in accordance with European approaches – particularly the GDPR and the MiCA Regulation – is substantiated. The relevance of forming a new paradigm of civil law is emphasized, one that ensures a balance between innovative development and the protection of fundamental rights. The article provides a comprehensive and in-depth analysis of the transformations occurring in civil law under the influence of the rapid development of digital technologies, artificial intelligence, and the overall digitalization of society. It highlights the emerging challenges faced by the national legal system due to the formation of new types of legal relations within the digital environment. Particular attention is paid to the need for a rethinking of the legal status of artificial intelligence, the development of new approaches to legal subjectivity, and the adaptation of contract and tort law norms to the realities of the digital age. The article focuses on the protection of personal data in the context of growing threats to the right to privacy, as well as the challenges associated with the use of automated decision-making algorithms. It examines recent legislative initiatives and reforms in Ukraine, including the introduction of the category of digital goods in the Civil Code of Ukraine, the adoption of the Law of Ukraine «On Digital Content and Digital Services», and the update of copyright legislation concerning works created without direct human involvement. The legal nature of virtual assets and cryptocurrencies is analyzed, along with a comparative legal assessment of their regulation in Ukraine and the European Union, particularly within the framework of the MiCA Regulation. The current state of the legal regime for digital assets, their classification, circulation features, and prospects for legal recognition are explored. The article substantiates the necessity of harmonizing national civil legislation with international legal standards, especially with the requirements of the European Union’s General Data Protection Regulation (GDPR). Emphasis is placed on the relevance of forming a new paradigm of civil law that takes into account the development of the digital economy, the need for effective legal regulation of innovative processes, and the imperative to ensure an adequate level of protection for fundamental human rights and freedoms. The conclusion underscores the necessity for further normative adaptation and the development of scientific doctrinal approaches to the determination of legal subjectivity, liability, and the balance of interests within the digital legal environment.